A Tale of Two Cities - "Dickens, Charles" (Longman: Hong Kong, 1995)
"The grim tale of the people who were caught up in the violence and murder of the French Revolution, in a controlled-vocabulary adaptation of Dicken's classic work."--Amazon.com viewed July 27, 2021
Keywords: Reading books Readers